Discovery of KDM5A inhibitors: Homology modeling, virtual screening and structure–activity relationship analysis. Issue 9 (1st May 2016) - Wu, Xiaoai; Fang, Zhen; Yang, Bo; Zhong, Lei; Yang, Qiuyuan; Zhang, Chunhui; Huang, Shenzhen; Xiang, Rong; Suzuki, Takayoshi; Li, Lin-Li; Yang, Sheng-Yong
Graphical abstract: Abstract: Herein we report the discovery of a series of new KDM5A inhibitors. A three-dimensional (3D) structure model of KDM5A jumonji domain was firstly established based on homology modeling. Molecular docking-based virtual screening was then performed against commercial chemical databases. A number of hit compounds were retrieved. Further structural optimization and structure–activity relationship (SAR) analysis were carried out to the most active hit compound, 9 (IC50 : 2.3 μM), which led to the discovery of several new KDM5A inhibitors. Among them, compound15e is the most potent one with an IC50 value of 0.22 μM against KDM5A. This compound showed good selectivity for KDM5A and considerable ability to suppress the demethylation of H3K4me3 in intact cells. Compound15e could be taken as a good lead compound for further studies.